Proposal for the creation of an institutional arrangement for the overall development of the agriculture sector of the Caribbean Community ([s.n.] [S.l.], 2001)
Proposes that a Regional Agricultural Development Coordination Unit (RADCU) should be established to replace CARDI. Indicates that the Unit would be integrated into the structure of the CARICOM Secretariat and be located in Guyana.
Keywords: AGRICULTURAL SECTOR